Conceptualising Learning Outcomes in Science at the Upper Primary Stage and its Integration in Classroom Processes - Koireng, R. R. (Voices of Teachers and Teacher Educators, 2019)
The paper discusses the conceptual ideas of learning outcomes in Science at the upper primary stage and how the learning outcomes are derived from the curriculum expectations. The paper also explains the broad nature of the learning outcome and how they are interdisciplinary in nature and involve crosscutting concepts. Further, the paper also illustrates some strategies to be adopted by teachers for integration of learning outcomes while transacting concepts in Science at the upper primary stage.